2017
DOI: 10.1038/eye.2017.120
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient-reported outcome and quality of life improvement following surgery for epiphora

Abstract: PurposeTo assess and compare the subjective improvement in symptoms and quality of life in adult patients who underwent commonly performed oculoplastic surgical interventions to treat epiphora.Materials and methodsA prospective study was undertaken involving all adult patients undergoing dacryocystorhinostomy (DCR), lid tightening (lateral tarsal strip or lateral wedge resection), and punctoplasty surgery at our institution. We assessed severity of epiphora preoperatively using the Munk score. At 3 months post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 18 publications
2
19
0
1
Order By: Relevance
“…For isolated intubation of the puncta lacrimalia, perforated punctum plugs may be used, while pure monocanalicular intubation can be performed using a Mini-Monoka. The monocanaliculonasal intubation systems include the Monoka (Wide Collarette type), Monoka of Fayet (Crawford type), the self-threading [1,2]. Neben Tränenfilmveränderungen, Lidfehlstellungen und Hypersekretion sind Störungen der ableitenden Tränenwege, insbesondere Tränenwegstenosen und Tränenwegverletzungen, eine der Hautpursachen für Epiphora [3,4].…”
Section: Introductionunclassified
“…For isolated intubation of the puncta lacrimalia, perforated punctum plugs may be used, while pure monocanalicular intubation can be performed using a Mini-Monoka. The monocanaliculonasal intubation systems include the Monoka (Wide Collarette type), Monoka of Fayet (Crawford type), the self-threading [1,2]. Neben Tränenfilmveränderungen, Lidfehlstellungen und Hypersekretion sind Störungen der ableitenden Tränenwege, insbesondere Tränenwegstenosen und Tränenwegverletzungen, eine der Hautpursachen für Epiphora [3,4].…”
Section: Introductionunclassified
“…Furthermore, different fixation techniques have been proposed 7,8 . The success rate of JT-CDCR varies from 57% to 98% in different studies 4,9 and there is great heterogeneity among outcomes evaluated to define the effectiveness of the procedure 3 . In our series, there were significantly more females subjected to CDCR (75%) with a mean age, similar to other studies, of 53 years 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopically-assisted placement of the JT gives the surgeon a chance to assess the proper position of the device and, later, tailor its length and angle to avoid painful mucosal contact or decubitus. Considering the presence of a permanent foreign body in the lacrimal canaliculum, it is mandatory to investigate patient discomfort and the ability of the JT to resolve symptoms related to the underlying pathology; while the majority of the published articles on JT conjunctivodacryocystorhinostomy (JT-CDCR) outcomes have focused on the primary surgery and initial success rate 3 , few studies have reported results exceeding one year postoperative and have not considered patient satisfaction and improvement of quality of life (QoL) 4 ; therefore, the purpose of this study was to evaluate results after a medium/long period of time and patient satisfaction through relief of symptoms and improved QoL using the Naso Lacrimal Duct Obstruction symptom-score (NLDO-SS).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, patency assessment based solely on Munk score can be misleading. Sipkowa et al [ 22 ], in post-operative assessment of patients after DCR without evident epiphora (0—Munk score), demonstrated very divergent Glasgow Benefit Inventory (GBI) scores. There is no consensus on the use of more detailed questionnaires because minor symptoms in some patients may not have a negative impact on their assessment of general or social status [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%